2017
DOI: 10.1007/s10803-016-3020-1
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Transition Planning Among Adolescents with Autism Spectrum Disorder

Abstract: Improving the health care transition process for youth with autism spectrum disorder (ASD) is critically important. This study was designed to examine the overall national transition core outcome among youth with ASD and each of the component measures of health care transition planning. Fewer than 10% of youth with ASD meet the national transition core outcome. Among youth with ASD, there is greater disparity in health care transition planning for non-Hispanic black youth, youth with family income <400% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In a small scale Canadian study, a group of adults with ASD self-reported on their health service use over a year, with 1/3 of young adults with ASD not having a single visit with a primary care provider (Vogan et al 2016 ). Given the higher rates of mental health problems, specific impairments in communication, and stress in unfamiliar situations (like hospital or ED) in adults with ASD, there is a need to offer holistic, proactive adult based care, similar to the medical home concept for children and adolescents (Walsh et al 2017 ). The rise in prevalence of ASD in children over the last decade means that there will be even greater numbers of young adults with ASD entering the adult healthcare system in the near future, and tools are needed to help physicians and families navigate this transition so that all of them can access proactive care (McGonigle et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a small scale Canadian study, a group of adults with ASD self-reported on their health service use over a year, with 1/3 of young adults with ASD not having a single visit with a primary care provider (Vogan et al 2016 ). Given the higher rates of mental health problems, specific impairments in communication, and stress in unfamiliar situations (like hospital or ED) in adults with ASD, there is a need to offer holistic, proactive adult based care, similar to the medical home concept for children and adolescents (Walsh et al 2017 ). The rise in prevalence of ASD in children over the last decade means that there will be even greater numbers of young adults with ASD entering the adult healthcare system in the near future, and tools are needed to help physicians and families navigate this transition so that all of them can access proactive care (McGonigle et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children or adolescents with special healthcare needs ‘have or are at increased risk for chronic physical, developmental, behavioral or emotional conditions and who also require health and related services of a type or amount beyond that required by children generally’ (McPherson et al, , p. 138). A recent study indicates that adolescents with special healthcare needs (ASHCN) regularly fall below the expectations of the national transition core outcomes for healthcare transition (Walsh, Jones, & Schonwald, ). Further, while research into general transition planning specifically for adolescents with intellectual and developmental disabilities (IDD) continues to grow (Burke, Wagner, Marolda, Quintana, & Maddux, ), research on healthcare‐specific transition planning has fallen behind (Kuhlthau et al, ; Walsh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicates that adolescents with special healthcare needs (ASHCN) regularly fall below the expectations of the national transition core outcomes for healthcare transition (Walsh, Jones, & Schonwald, ). Further, while research into general transition planning specifically for adolescents with intellectual and developmental disabilities (IDD) continues to grow (Burke, Wagner, Marolda, Quintana, & Maddux, ), research on healthcare‐specific transition planning has fallen behind (Kuhlthau et al, ; Walsh et al, ). Disparities also currently exist between individuals of differing race and disabilities in terms of the type of support and transitioning services they receive (Kuhlthau et al, ; Walsh et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations